THE CONSUMER PERCEPTION ON QUALITY OF THE PEARL JEWELRY CRAFTS PRODUCTS MATARAM - Muhamad Ilhamuddin; Santi Nururly; Rusminah Rusminah; Hilmiati Hilmiati (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The research aims to determine consumer perception on the quality of pearl jewelry products in Mataram. The population is consumers of pearl jewelry products, and the respondent determination technique is purposive sampling. The number of sample taken is 100 people. To answer the problem posed, the Ideal-Point Model is used. The model measures the gap (difference) between what is perceived and what consumers need. The result shows that the interest of consumers in purchasing pearl jewelry is mainly due to pearl quality, followed by other quality attributes. The quality value gap is quite large in the attributes of conformity to specifications, frame material, aesthetic value, price, and pearl jewelry design. Even though there is a value gap in some quality attributes, overall quality of Sekarbela pearl jewelry products is very good according to consumer perception.Keywords:Perception, Consumer, Quality, Crafts, Pearls